Universiti Malaysia Sarawak Contribution Towards Biodiversity and Protected Area Management - MT, Abdullah; Andrew Alek, Tuen; Faisal Ali, Anwarali Khan (Sarawak Forestry Cooperation, 2005)
The Convention on Biological Diversity (CBD) Article 13 addresses the aspects of public education that requires the Parties to promote and encourage understanding on the conservation of biological diversity; and cooperate in developing educational programmes with respect to onservation and sustainable use of biological diversity. During the recent 7th Meeting of the Conference of the Parties (COP 7), held in Kuala Lumpur in 2004, the Parties had reaffirmed the CBD to include the biological diversity of mountain ecosystems, ...